Analysis of Development of Traditional International Criminal Legislation: The Impact of International Criminal Law on Public International Law and Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The rise of international criminal law has been one ofthe remarkable features of international law since 1990. One of theless-explored questions of international criminal law is its social effects,within the international community and the community of public internationallaw, in other parts and activities of international law. In particular, whatare the effects of the rise of international criminal law and its emergingsystem of tribunals on the rest of the laws of armed conflict? What are theeffects upon apparently unrelated aspects of humanitarian and human rights law?What are the effects upon other large systems and institutions of publicinternational law, such as the UN and other international organizations? Asinternational criminal law has emerged as a visible face of publicinternational law, has it supplanted or even ‘crowded’ other aspects and institutionsof public international law? This brief study offers a high-altitude,high-speed look at the effects of international criminal law on other parts ofpublic international law and organizations.